UJI IN VIVO TIKUS WISTAR DENGAN BIT MERAH (Beta vulgaris L ) UNTUK PERBAIKAN KELAINAN PROFIL DARAH AKIBAT PAPARAN PESTISIDA: - - Kartika - Ikawati (LPPM Universitas Abdurrab, 2023)
Pesticides increase the number of free radicals, triggering oxidative stress causing inflammation and blood profile abnormalities such as anemia, agranulocytosis, neutropenia and thrombopenia. One of the plants that is rich in antioxidants and nutrients to form blood cells is red beet (Beta vulgaris L). The purpose of this study was to determine the ability of red beet (Beta vulgaris L) to improve blood profile abnormalities due to pesticide exposure through in vivo test of Wistar male rats. This research is a laboratory experimental type with a Post Test Only Randomized Control Group Design. The sample of the study was 25 male Wistar rats which were randomly divided into 5 different treatment groups. Mice were exposed to 140 ml/day of pesticides and various doses of red beet ethanol extract for 14 days. The blood profile parameters examined were hemoglobin level, hematocrit, erythrocyte count and leukocyte count. Examination of blood profile parameters manually and automatically. Data analysis with ANOVA and Post Hoc tests. The results of the study proved that the ethanol extract of red beetroot was able to improve blood profile damage due to pesticide exposure in the form of a significant increase in hemoglobin levels, hematocrit values, erythrocyte counts and reduced leukocyte counts from leukocytosis (P<0.05). The optimal dose of red beet ethanol extract is 400 mg/kgBB. Red beets are able to improve blood profile abnormalities due to exposure to pesticides. Red beets are recommended as a non-pharmacological alternative to improve blood profile abnormalities due to exposure to pesticides.